Maxwell-Higgs self-dual solitons on an infinite cylinder - Casana, Rodolfo (2015)
We have studied the Maxwell-Higgs model on the surface of an infinite cylinder. In particular, we show that this model supports self-dual topological soliton solutions on the infinite tube. Finally, the Bogomol'nyi-type equations are studied from theoretical and numerical point of view.